Opioid Receptor-Mediated and Non-Opioid Receptor-Mediated Roles of Opioids in Tumour Growth and Metastasis - Scroope, Claudia A.; Singleton, Zane; Hollmann, Markus W.; Parat, Marie-Odile (Frontiers in Oncology, 2021)
Opioids are administered to cancer patients in the period surrounding tumour excision, and in the management of cancer-associated pain. The effects of opioids on tumour growth and metastasis, and their consequences on disease outcome, continue to be the object of polarised, discrepant literature. It is becoming clear that opioids contribute a range of direct and indirect effects to the biology of solid tumours, to the anticancer immune response, inflammation, angiogenesis and importantly, to the tumour-promoting effects of pain. A common misconception in the literature is that the effect of opioid agonists equates the effect of the mu-opioid receptor, the major target of the analgesic effect of this class of drugs. We review the evidence on opioid receptor expression in cancer, opioid receptor polymorphisms and cancer outcome, the effect of opioid antagonists, especially the peripheral antagonist methylnaltrexone, and lastly, the evidence available of a role for opioids through non-opioid receptor mediated actions.